Sporting Mega-Events as Catalysts for Sustainability and Tourism Development in Russia - DEDUSENKO, Elena Aleksandrovna (Journal of Environmental Management and Tourism, 2019)
The idea of this paper is to discuss the impact of sporting mega-events for sustainability and tourism development in Russia. The paper deals with the issues of complex influence of international sports events on society, economy, environment and tourism. In the context of international trends and experience, it is important for Russia to take into account further opportunities and long-term effects of sports events in various spheres of the country. These features can be implemented in practice using public-private partnerships, cooperation of various management levels of the state authorities, involvement of stakeholders and attention to the e-sports market. Given the high financial costs of organizing and conducting such events, it is valuable to focus on the intangible benefits of sporting events.